The In-Out dispositional affective style questionnaire (IN-OUT DASQ): an exploratory factorial analysis - Mazzola, Viridiana; Marano, Giuseppe; Biganzoli, Elia M.; Boracchi, Patrizia; Lanciano, Tiziana; Arciero, Giampiero; Bondolfi, Guido (Frontiers in Psychology, 2014)
The issue of individual differences has always been an important area of research in psychology and, more recently, neuroimaging. A major source of interindividual variability stems from differences in basic affective dispositions. In order to make a contribution to this field of research, we have developed a new type of assessment - the In-Out Dispositional Affective Style Questionnaire (IN-OUT DASQ) - to measure the proneness between two different ways of feeling situated: a predominantly body-bound one in the case of the inward tendency and an externally anchored one in the case of the outward tendency (Arciero and Bondolfi, 2009). The IN-OUT DASQ contains 2 scales of 7 items each, Self-centric engagement (SCE) and Other-centric engagement (OCE), as a disposition index for inwardness and outwardness respectively. The exploratory factor analysis in sample 1 (n= 292) confirmed a two-factor solution. Confirmatory factor analysis in sample 2 (n= 300) showed the good fit of this two-factor model. Next, we examined construct validity also investigating the correlations between the IN-OUT DASQ, the Big Five Questionnaire and the Positive and Negative Affect Schedule in sample 3 (n=153). The SCE and OCE scales had robust internal consistency and reliability, and therefore the capacity to discriminate higher inward and outward participants was stronger in SCE. Although further validation research is required, the present study suggests the IN-OUT DASQ has the potential to be a measurement tool for detecting individual differences in social behavior and social affective neuroscience.